2019
DOI: 10.1016/j.ijthermalsci.2019.106099
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase flow and boiling heat transfer modelling of nanofluids in horizontal tubes embedded in a metal foam

Abstract: The aim of this numerical study is to evaluate the boiling process of nanofluid in horizontal tubes in the presence of a metal foam as a porous medium and represent the experimental work of Zhao et al. in a numerical aspect with a different range of dependent variables. High conductive metal foams are employed to increase the rate of heat transfer and enhance the boiling performance in the domain. The two-phase mixture model is used to simulate the characteristics of nanofluid and solve the governing equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 75 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…The parameters of porous media such as porosity ε, inertia coefficient C d and permeability K are reported in references 27 – 30 . …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of porous media such as porosity ε, inertia coefficient C d and permeability K are reported in references 27 – 30 . …”
Section: Methodsmentioning
confidence: 99%
“…Effective thermal conductivity is influenced by nanofluid thermal conductivity and the copper porous conductivity and is given as follows 27 , 30 : …”
Section: Methodsmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) modeling of the nanofluid flows in porous media has been commonly used by studies 26 , 27 for the prediction of the flow characteristics. However, the CFD method, alone, is not a perfect way, especially in complicated cases (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Substitutes for PCM have been developed recently by the composite metal foam/PCM to enhance the heat transfer inside PCM [ 6 , 7 ]. A study by Mesalhy et al [ 8 ] showed that the porous foam matrix within PCM has a significant impact on the rate of heat transfer and charging time.…”
Section: Introductionmentioning
confidence: 99%